Topological version of generalized (infinite) iterated function systems. (February 2015) - Dumitru, Dan; Ioana, Loredana; Sfetcu, Răzvan-Cornel; Strobin, Filip
Abstract: Our paper is an attempt to unify various generalizations of IFSs which appeared in the literature in the last years. We extend the notion of a generalized iterated function system (introduced by Miculescu and Mihail in 2008) to the topological and (possible) infinite case. Then we prove that many classical results (for example the existence of a unique attractor) hold for this extended case.